MULTIMEDIA-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING MODEL IN IMPROVING STUDENT ACHIEVEMENT (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Education is a conscious and planned process aimed at developing the personality, attitudes, and abilities of students holistically, both physically and spiritually. Along with technological advancements, learning has undergone transformations, one of which is through the use of multimedia, which is considered capable of increasing the effectiveness of material delivery. This study aims to describe the implementation of a multimedia-based Islamic Religious Education (PAI) learning model at Al-Azhar Cairo Islamic Junior High School in Banda Aceh and the challenges encountered during this process. The method used was a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results showed that the use of digital devices such as iPads, Apple TVs, and the Keynote application increased students' interest in learning and understanding of PAI material. The strategies implemented included technical preparation, multimedia project implementation, and the use of interactive presentation media. However, several obstacles hampered the learning process, such as unstable internet connections, limited learning platforms for PAI subjects, and student dependence on digital devices. This study concluded that multimedia-based learning can be an effective alternative for improving the quality of PAI learning if supported by adequate infrastructure, teacher training, and digital classroom management that balances technology and direct interaction